Bibliometric Analysis of Problem-Based Learning Model with STEM Approach: Critical Thinking Skills of Elementary School Students - Azhari, Rafa Adilla; Hidayah, Nurul; Diani, Rahma; Kalifah, Diah Rizki Nur (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Elementary schools must creatively develop critical thinking abilities to equip students with 21st-century competencies. Analyzing previous research on integrating learning models for this purpose is necessary. This study will bibliometrically analyze the research on integrating the Problem-Based Learning (PBL) model with the Science, Technology, Engineering, and Mathematics (STEM) approach to improve elementary school critical thinking. VOSviewer software was used to conduct a systematic literature review and bibliometric analysis of 52 Scopus-indexed articles from 2020–2024. Publish or Perish (PoP), linked to Scopus, collected publication data using "problem-based learning," "STEM," "critical thinking," and "elementary school." The literature review found that the STEM-integrated PBL model in elementary schools improves critical thinking and student learning by providing real-world problems to solve. Indonesia contributed 30 articles, followed by the US (5 articles) and Hong Kong (3 articles). The study's five-year collaboration network includes 69 researchers. Bibliometric analysis indicated a high association between "STEM" and "critical thinking" and "learning model," showing that STEM influences critical thinking skills. The association between "problem-based learning," "learning model," and "critical thinking" showed that PBL strongly impacts these skills. But network visualization revealed a research gap in the weak and narrow connections between "STEM," "Problem-Based Learning," and "Elementary School." The first co-occurrence analysis showed "critical thinking," followed by "problem-based learning" and "STEM." The rise of "bibliometric analysis" and "elementary school" suggests elementary education research is digitizing. In conclusion, STEM-integrated PBL has worked, but further research is needed to apply it to elementary school pupils.